Promising CoSe2-CNT composite catalyst for efficient photoelectrochemical hydrogen evolution reaction - Pi, Zhi-Gang; Ye, Hongfeng; Han, Zuqi; Yu, Peng; Yin, Zhuoxun; Ma, Xinzhi (Frontiers in Materials, 2022)
CoSe2 is a typical transition metal chalcogenide and an hydrogen evolution reaction hydrogen evolution catalyst due to its efficient and inexpensive characteristics. In this work, CoSe2/CNT composite was synthesized through a one-step solvothermal method. Specifically, a current density of 10 mA cm−2 can be achieved under an overpotential of 163 mV, and the Tafel slope is 69.4 mV dec−1. The reasons for these excellent performances are: 1) the abundant catalytic active sites of CoSe2; 2) the high conductivity of CNTs; and 3) the synergistic effect between CoSe2 and CNTs; iv the solar irradiation excites electrons to join the reaction. This work proposes a new way to reasonably design the high-efficiency and low-cost transition metal chalcogenide hydrogen evolution catalysts.